The embryological characteristics and clinical outcomes of oocytes with indented zona pellucida - Jie Lin; Lu Fang; Lv Yao; Haichao Wang; Hongyan Lan; Yinli Zhang; Xiaomei Tong (Journal of Obstetrics and Gynaecology)
Background Our study aimed to investigate the embryological characteristics and clinical outcomes of oocytes with indented zona pellucida (iZP).Methods Cases with all oocytes containing iZP were compared with subjects whose oocytes presented morphologically normal ZP (nZP, controls), regarding embryological and clinical outcomes. Cases consisted of 56 subjects that underwent 109 assisted reproductive treatment (ART) cycles, and controls were made of 574 patients that were enrolled in 1095 ART cycles.Results Patients with iZP presented a significantly prolonged duration of infertility and were more likely to have primary infertility. Regarding embryonic development, cases with iZP evidenced significantly lower rates of retrieved oocytes, oocyte maturity, fertilisation, embryo cleavage, high-quality embryo and blastocyst (p < .05). Relatively to clinical outcomes, 32 patients with iZP underwent fresh embryo transfer. Compared to controls, the rates of clinical pregnancy (CP) (43.8% vs. 65.9%, p = .014) and live-birth delivery (LBD) (34.4% vs. 58.5%, p = .009) were significantly lower. No significant differences were observed between groups regarding clinical outcomes after frozen–thawed embryo transfer (FET). However, cumulative rates elicited excellent CP (49.3%) and LBD (42.0%) rates in cases with iZP. In cases where rescue-intracytoplasmic sperm injection (ICSI) was needed, cases with iZP could achieve lower but nevertheless high cumulative CP (52.6%) and LBD (36.8%) rates.Conclusions Patients with iZP present satisfactory embryological and clinical outcomes, with ICSI and FET cycles improving the global outcomes.